Therapeutic Communities for Addictions: A Review of Their Effectiveness from a Recovery-Oriented Perspective. (16th December 2012) - Vanderplasschen, Wouter; Colpaert, Kathy; Autrique, Mieke; Rapp, Richard Charles; Pearce, Steve; Broekaert, Eric; Vandevelde, Stijn
Abstract : Therapeutic communities (TCs) for addictions are drug-free environments in which people with addictive problems live together in an organized and structured way to promote change toward recovery and reinsertion in society. Despite a long research tradition in TCs, the evidence base for the effectiveness of TCs is limited according to available reviews. Since most of these studies applied a selective focus, we made a comprehensive systematic review of all controlled studies that compared the effectiveness of TCs for addictions with that of a control condition. The focus of this paper is on recovery, including attention for various life domains and a longitudinal scope. We searched the following databases: ISI Web of Knowledge (WoS), PubMed, and DrugScope. Our search strategy revealed 997 hits. Eventually, 30 publications were selected for this paper, which were based on 16 original studies. Two out of three studies showed significantly better substance use and legal outcomes among TC participants, and five studies found superior employment and psychological functioning. Length of stay in treatment and participation in subsequent aftercare were consistent predictors of recovery status. We conclude that TCs can promote change regarding various outcome categories. Since recovering addicts often cycle between abstinence and relapse, a continuing care approach is advisable, including assessment of multiple and subjective outcome indicators.